Dreamworks The epic tales of Captain Underpants. The maniacal mischief of the marauding monsters - Rusu, Meredith (New York, NY : Scholastic Inc., 2023)
No one loves Halloween more than George Beard and Harold Hutchins. Join the two best friends and their superhero pal, Captain Underpants, in this terrifying and totally funny two-story collection! First, George and Harold go teeth-to-teeth against a ghost dentist when their spooky campfire story comes to life! Then, George and Harold have to face a terrifying T.P. mummy after their most epic prank ever goes down the drain. Can Captain Underpants flush away these vile villains so George and Harold can live to prank another day?
The ghastly danger of the ghost dentist -- The terrifying perilous misfortune of the TP mummy.
May include stickers.
2.6
K-3
GN460L
Keywords: Captain Underpants -- (Fictitious character) -- Comic books, strips, etc; Captain Underpants -- (Fictitious character) -- Juvenile fiction; Superheroes -- Comic books, strips, etc; Superheroes -- Juvenile fiction; Halloween -- Comic books, strips, etc; Halloween -- Juvenile fiction; Ghosts -- Comic books, strips, etc; Ghost stories; Dentists -- Comic books, strips, etc; Dentists -- Juvenile fiction; Mummies -- Comic books, strips, etc; Mummies -- Juvenile fiction; Humorous stories; Superheroes -- Fiction; Halloween -- Fiction; Ghosts -- Fiction; Dentists -- Fiction; Mummies -- Fiction; Superhero comics; Ghost comics; Humorous comics; Graphic novels